Reproductive Health Services for Adolescents With Hearing Impairment in Indonesia: Expectations and Reality - Ni Luh Putu Suariyani; Desak Putu Yuli Kurniati; Desak Nyoman Widyanthini; Luh Putu Wulandari Artha (Korean Society for Preventive Medicine, 2020)
Objectives Reproductive health education is essential for adolescents with hearing impairment. Since they communicate using specialized language (i.e., sign language), specialized reproductive health services in sign language is a necessity. This study aimed to describe the needs, availability, and expectations of reproductive health services among adolescents with hearing impairment. Methods This study used a qualitative approach. It was carried out at a school for children with special needs in the city of Denpasar, Bali, Indonesia. Data were collected by in-depth interviews. The informants were 6 adolescents with hearing impairment aged 16-17 years and 4 other key informants, including school staff and health officers. The data were then analyzed using the thematic method. Results We found that the informants had insufficient knowledge regarding reproductive health. There was no specific subject in the curriculum regarding this issue. Teachers did not specifically provide reproductive health information. The health service unit in the school had not been utilized well for this purpose. Furthermore, no reproductive health services were provided due to the limited number of healthcare workers who could use sign language. Conclusions The awareness and intentions of adolescents with hearing impairment regarding access to reproductive health services remain low. Health service units at schools should be optimized to enable schools to provide reproductive health information and services for these adolescents.